Acid-base balance at lactate threshold in resistance exercise - de Sousa, N.M.F.; Magosso, R.F.; Arakelian, V.M.; Pereira, G.B.; Domingos, M.M.; Perez, S.E.A.; Baldissera, V. (Science & Sports, 2013)
Objective: To evaluate acid-base status during constant-load resistance exercise at the lactate threshold (LT) intensity. Methods: Seven healthy men underwent two protocols on a leg press machine. One maximal incremental test to determine LT intensity and a constant-load resistance protocol executed at this intensity. The participants performed 15 sets of 20 repetitions lasting 1 min with 1 min rest intervals during the constant-load exercise. Capillary blood samples were collected during the tests in order to evaluate blood lactate concentration, pH, bicarbonate, base excess, peripheral blood gas levels and oxygen saturation. Results: Blood lactate concentration increased significantly (P = 0.017; significant level with Bonferroni correction) between rest (0.65 ± 0.21 mmol.L-1) and set 15 (4.58 ± 1.96 mmol.L-1). Blood lactate concentration remained stable during the constant-load resistance exercise (P > 0.017). Bicarbonate, base excess and partial pressure of carbon dioxide had a significant decrease (26.4 ± 2.1 mmol.L-1, 2.7 ± 2.4 and 36.0 ± 2.7 mmHg at rest, respectively, to 19.6 ± 4.3 mmol.L-1, -5.0 ± 3.4, 30.2 ± 4.0 mmHg at set 15, respectively; P = 0.017). Oxygen saturation and pH also remained constant during the exercise (97.2 ± 1.8% and 7.47 ± 0.03 at rest to 97.0 ± 1.4 and 7.41 ± 0.05 at set 15, respectively; P > 0.017). Conclusion: During a constant-load resistance exercise at LT intensity pH remained constant and this intensity seems to correspond to a metabolic steady state.